1992
DOI: 10.1038/360264a0
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan of human lymphocyte subsets defined by CD45 isoforms

Abstract: The lifespan of thymic-derived or T lymphocytes is of particular interest because of their central role in immunological memory. Is the recall of a vaccination or early infection, which may be demonstrated clinically up to 50 years after antigen exposure, retained by a long-lived cell, or by its progeny? Using the observation that T lymphocyte expression of isoforms of CD45 corresponds with their ability to respond to recall antigens, we have investigated the lifespan of both CD45R0 (the subset containing resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

34
350
2
8

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 600 publications
(394 citation statements)
references
References 14 publications
34
350
2
8
Order By: Relevance
“…Although the relative contributions of different cytokines to homeostatic proliferation in humans are difficult to address directly, recent reports are consistent with the view that human and murine T cells have similar requirements [13,14,21,[28][29][30][31][32]. Thus, antigen-independent naive T cell proliferation in the mouse requires TCR tickling, IL-7, and lymphopenia, whereas CD8 memory T cells turn over constitutively, express high levels of the IL-2/ 15Rb chain and require IL-15 or IL-7.…”
Section: Discussionsupporting
confidence: 57%
“…Although the relative contributions of different cytokines to homeostatic proliferation in humans are difficult to address directly, recent reports are consistent with the view that human and murine T cells have similar requirements [13,14,21,[28][29][30][31][32]. Thus, antigen-independent naive T cell proliferation in the mouse requires TCR tickling, IL-7, and lymphopenia, whereas CD8 memory T cells turn over constitutively, express high levels of the IL-2/ 15Rb chain and require IL-15 or IL-7.…”
Section: Discussionsupporting
confidence: 57%
“…The dim CD45RA þ ,CD45RO þ 62 P. S. Mattila double-positive population fulfils both of these expectations: first, the dim CD45RA þ ,CD45RO þ double-positive population was more numerous than the bright CD45RA þ ,CD45RO þ double-positive population and second, the dim CD45RA þ , CD45RO þ double-positive population was more frequent in peripheral blood than in the adenoids. The re-expression of CD45RA has been reported to occur without cell division [18], therefore this transition may occur more frequently in quiescent circulating cells than in cells residing in secondary lymphoid organs, such as the adenoids. However, all that can be concluded is that the dim CD45RA þ ,CD45RO þ double-positive population is more frequent in peripheral blood than in adenoidal tissue, and that the ontogeny of this cell population still remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…These two populations of cells have been proposed to represent 'naive' and 'memory' T cells, respectively. However, it has been suggested that CD45RO þ cells can revert to express the CD45RA isoform [16][17][18][19][20]. Thus, the isoform switch may not be irreversible, and the CD45 isoform phenotype may rather imply that the CD45RA þ population represents quiescent T cells, whereas the CD45RO þ subset contains recently activated T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Answering this question hinges on understanding the kinetic behavior of memory cells and the factors that regulate their life span. In this regard, studies in animals and humans have revealed that the majority of T cells with a memory phenotype (CD44 high in mice) exhibit a rapid rate of turnover (2)(3)(4)(5)(6). This was also shown to apply to memory T cells of known antigenic specificity using TCR-transgenic mice (7,8).…”
mentioning
confidence: 93%